2019
DOI: 10.1038/s41598-019-45669-z
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Bystander Effect is Mediated by Mitochondrial DNA in Exosome-Like Vesicles

Abstract: Exosome-like vesicles (ELV) are involved in mediating radiation-induced bystander effect (RIBE). Here, we used ELV from control cell conditioned medium (CCCM) and from 4 Gy of X-ray irradiated cell conditioned medium (ICCM), which has been used to culture normal human fibroblast cells to examine the possibility of ELV mediating RIBE signals. We investigated whether ELV from 4 Gy irradiated mouse serum mediate RIBE signals. Induction of DNA damage was observed in cells that were treated with ICCM ELV and ELV fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 66 publications
0
43
2
Order By: Relevance
“…A similar study demonstrated the tumourigenic effects of EV mtDNA in potentiating the radiation-induced bystander effect, in which the phenotype of irradiated cells is transferred to non-irradiated "bystander" cells. Using DNase treatment and mitochondrial depletion assays, EV mtDNA from irradiated cells was shown to play a key role in inflicting chromosomal instability on nearby non-irradiated cells 92 . However, the molecular mechanism by which EV mtDNA induced phenotypic changes in recipient cells was not investigated.…”
Section: Transfer Of Genetic Materialsmentioning
confidence: 99%
“…A similar study demonstrated the tumourigenic effects of EV mtDNA in potentiating the radiation-induced bystander effect, in which the phenotype of irradiated cells is transferred to non-irradiated "bystander" cells. Using DNase treatment and mitochondrial depletion assays, EV mtDNA from irradiated cells was shown to play a key role in inflicting chromosomal instability on nearby non-irradiated cells 92 . However, the molecular mechanism by which EV mtDNA induced phenotypic changes in recipient cells was not investigated.…”
Section: Transfer Of Genetic Materialsmentioning
confidence: 99%
“…Mechanistically, IR causes changes in exosomal secretion patterns and content of exosomal cargo of the target cells, which can cause RIBE in the bystander cells as shown in several in vitro studies. [30,32,[37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon was defined as radiation-induced bystander effect (RIBE), which now refers to the plethora of biological phenomena, occurring in nonirradiated cells because of signal transmission from irradiated cells [ 3 ]. RIBE can be mediated by soluble factors, such as cytokines or reactive oxygen species (ROS) [ 3 ], which can be released from the cells or can be transported through gap junctions [ 4 ], or packed into extracellular vesicles in order to travel to the neighboring cells [ 5 ]. In neighboring cells, RIBE was demonstrated to be connected to several hallmarks of cancer and can act like a double-edged sword mediating antitumor or protumor responses [ 3 ].…”
Section: Introductionmentioning
confidence: 99%